Tisza István szobrának felavatása és újraavatása Debrecenben – 1926, 2000 - Pallai, László (Gerundium, 2017)
The Inauguration and Repeated Inauguration of the Statue of István Tisza in Debrecen: 1926 and 2000. Between 1921 and 1945, the name-giver of the University of Debrecen was István Tisza. Tisza’s personality and political aura were bound up with Debrecen, and he played a decisive role in the establishment of the university. Soon after his death (1918) a sort of Tisza cult began to take shape in Debrecen and he became not only a university name-giver; he was also given a statue on the campus of the university. With the aid of contemporaneous documents and photoes, the present survey highlights the events of the 1926 inauguration celebration of the statue, then follows up its fate from the Second World War up to the year 2000, i.e. from the toppling of the statue to its repeated inauguration.